45.0k views
2 votes
Solve the following quadratic by

completing the square.
f(x) = x² + 2x - 12
+√[]
x = [?] +

1 Answer

3 votes

Answer:

{x = -1 + √13 , x = -1 - √13}

Explanation:

Completing the square:

f(x) = x² + 2x - 12

= x² + 2x + 1 - 1 - 12

= (x² + 2x + 1) - 1 - 12

= (x + 1)² - 13

Solving:

f(x) = 0

⇔ (x + 1)² - 13 = 0

⇔ (x + 1)² = 13

⇔ x + 1 = √13 or x + 1 = -√13

⇔ x = -1 + √13 or x = -1 - √13

User Hasib
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.